Analisis Faktor Mutu Pelayanan terhadap Minat Kunjung Ulang Pasien Rawat Jalan Di RSU Royal Prima Medan Tahun 2022 - Agung Prawira Chandra; Chrismis Novalinda Ginting; Santy Deasy Siregar (Journal of Health Science and Prevention, 2023)
Patient satisfaction levels are a good sign of how well a hospital provides services. The likelihood that a patient will return increases if they are satisfied with the hospital's services, which obviously benefits the facility. In this study, Royal Prima Medan outpatients' intentions to return to RSU were examined in relation to several service quality metrics. A cross-sectional design was used for this analytical survey research study. The study's population consisted of 4,011 average outpatients at the Pulmonary and Cardiac Polyclinic from July to August 2022. A sample of 98 respondents using an unintended sampling strategy was drawn from this cohort. Methods for univariate, bivariate, and multivariate data analysis were used in this study. The findings showed that the intention to return to the hospitalized patients road was influenced by the variable quality of infrastructure (sig-p = 0.004 0.05), the variable quality of human resources (sig-p = 0.025 0.05), and the variable quality of security (sig-p = 0.015 0.05), whereas the personal quality variables (sig-p = 0.054 > 0.05, gender = 0.253 > 0.05, education = 0.322 > 0.05, and occupation) were not.. According to the study's conclusions, it is thought that providing health staff training, reducing patient costs for less fortunate patients, and creating an organizational structure focused n duties and education will all enhance the hospital.